Analisis pendapatan pelaku UMKM di sekitar kawasan taman sanggar batik Kota Jambi - Adji Permana; Zulfanetti; Rosmeli (PT. Saha Kreasi Indonesia, 2026)
This study aims to analyze the effect of capital, working hours, labor, and type of merchandise on the income of Micro, Small, and Medium Enterprises (MSMEs) in the Taman Sanggar Batik area of Jambi City. This research employs a quantitative approach using multiple linear regression analysis. The type of merchandise is categorized into batik and non-batik using a dummy variable. The data were collected from 42 MSME respondents through questionnaires and direct interviews. The results show that most MSME owners are male, have a senior high school education background, and are in the productive age group of 36–45 years, with an average age of 41.50 years. The average number of dependents is 2 persons. Most MSMEs operate for 7–8 hours per day, with an average working time of 7.98 hours, employ a relatively small number of workers with an average of 2 persons, and have an average business capital of Rp5,226,190. The average MSME income is Rp2,202,381 per month. Although the number of batik and non-batik MSMEs is equal, batik MSMEs earn a higher average income. The regression analysis indicates that capital and type of merchandise have a significant effect on MSME income. Meanwhile, working hours have no significant effect on income, and labor has an effect but is not statistically significant. These findings suggest that capital and type of merchandise are the main factors influencing MSME income in the Taman Sanggar Batik area of Jambi City.